PENGARUH KUALITAS AUDIT, KARAKTERISTIK KOMITE AUDIT, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TIMELINESS LAPORAN KEUANGAN: Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia - Yustika Panggabean; Julian Maradina (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine and find empirical evidence of the effect of audit quality, audit committee characteristics and institutional ownership on the timeliness of financial statements. The method used in this research is associative quantitative research and uses secondary data in the form of annual financial reports obtained from the official website of the Indonesia Stock Exchange. The population in this study are all mining sector companies listed on the Indonesian Stock Exchange. The sample was selected using a purposive sampling technique through predetermined criteria. The total sample used in this study amounted to 60 data with a research period of 5 years. The analytical method used in this study is multiple linear analysis with the help of the e-views 9 program. The results show that auditor quality affects the timeliness of financial reports while audit committee size, frequency of audit committee meetings and institutional ownership do not affect the timeliness of financial reports